Latin American Television: A Global View - Sinclair, John (Oxford University Press, 1998)
Latin American Television makes English speakers aware of the dimensions, operation, and significance of the globalization of television in the Spanish-speaking world. Second only in scale to the market for English-language programming, the Spanish-language market embraces not just most nations of South and Central America but also Spain, and even the United States–the sixth largest Spanish-speaking country in the world. This intercontinental space is connected physically by satellite communication, and culturally by a common language and heritage which binds it as both a `geolinguistic region' and an `imagined community' which certain media corporations, Latin American and North American, seek to exploit. A similar phenomenon with regard to Brazil and the Portuguese-speaking world is ... Source: Publisher
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

From Quinceañera to Miss XV: Coming of Age in Mexican Screen Melodrama - Rios, Sofia (Children, Youth, and International Television, 2022)
This chapter historicises and contextualises the evolution, production, and development of key Mexican screen melodramas over fifty-two years to understand and mediate Mexico’s ambivalence around socioeconomic background, ranother. Perhaps if Televisa had allowed its various ace and religion, gender and worth, family and duty. The chapter demonstrates the importance of localised scholarly inquiry into Mexican audiovisual media that considers not only narrative discourses, content and textual analyses, but also industrial records and practices, marketing campaigns and press releases, archival research and interviews, multimedia synergy, and comparative analysis. For some time, research on Mexican melodrama has had a strong social focus, with several writings about audience engagement, but it is imperative to have more close readings of the texts themselves to understand their cultural context and industrial histories. This research exposes societal changes within Mexico by utilising one of its most omnipresent forms of popular culture and provides a deeper understanding of Mexico’s primary media productions through the use of genre and remake theory. The representations of young women yield a multitude of tensions and ambiguities placed upon Mexican women, which reveal volumes about wider sociocultural expectations.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Mexican Genders, Mexican Genres: Cinema, Television, and Streaming Since 2010 - Smith, Paul Julian (Boydell & Brewer, 2021)
Gender and the contemporary audio-visual landscape of Mexico.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Evolution of Black Women in Television: Mammies, Matriarchs and Mistresses - Cheers, Imani M. (Routledge, 2017)
This book seeks to interrogate the representation of Black women in television. Cheers explores how the increase of Black women in media ownership and creative executive roles (producers, showrunners, directors and writers) in the last 30 years affected the fundamental cultural shift in Black women’s representation on television, which in turn parallels the political, social, economic and cultural advancements of Black women in America from 1950 to 2016. She also examines Black women as a diverse television audience, discussing how they interact and respond to the constantly evolving television representation of their image and likeness, looking specifically at how social media is used as a tool of audience engagement.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Television Drama in Spain and Latin America : Genre and Format Translation - Julian Smith, Paul (Institute of Modern Languages Research, 2020)
Television Drama in Spain and Latin America addresses two major topics within current cultural, media, and television studies: the question of fictional genres and that of transnational circulation. While much research has been carried out on both TV formats and remakes in the English-speaking world, almost nothing has been published on the huge and dynamic Spanish-speaking sector. This book discusses and analyses series since 2000 from Spain (in both Spanish and Catalan), Mexico, Venezuela, and (to a lesser extent) the US, employing both empirical research on production and distribution and textual analysis of content. The three genres examined are horror, biographical series, and sports-themed dramas; the three examples of format remakes are of a period mystery (Spain, Mexico), a romantic comedy (Venezuela, US), and a historical epic (Catalonia, Spain). Paul Julian Smith is Distinguished Professor at the Graduate Center, City University of New York. He was previously Professor of Spanish at the University of Cambridge. He is the author of twenty books and one hundred academic articles.
Accepted: 2022-06-02T04:31:38Z Journal Abbreviation: Genre and Format Translation
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Espagne (corpus analysé); Mexique (corpus analysé); Venezuela (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé

Pimpin' Ain't Easy: Selling Black Entertainment Television - Smith-Shomade, Beretta E. (Routledge, 2007)
Launched in 1980, cable network Black Entertainment Television (BET) has helped make blackness visible and profitable at levels never seen prior in the TV industry. In 2000, BET was sold by founder Robert L. Johnson, a former cable lobbyist, to media giant Viacom for 2.33 billion dollars. This book explores the legacy of BET: what the network has provided to the larger US television economy, and, more specifically, to its target African-American demographic. The book examines whether the company has fulfilled its stated goals and implied obligation to African-American communities. Has it changed the way African-Americans see themselves and the way others see them? Does the financial success of the network - secured in large part via the proliferation of images deemed offensive and problematic by many black communities - come at the expense of its African-American audience? This book fills a major gap in black television scholarship and should find a sizeable audience in both media studies and African-American studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Black, White, and in Color: Television and Black Civil Rights - Torres, Sasha (Princeton University Press, 2018)
This book examines the representation of blackness on television at the height of the southern civil rights movement and again in the aftermath of the Reagan-Bush years. In the process, it looks carefully at how television's ideological projects with respect to race have supported or conflicted with the industry's incentive to maximize profits or consolidate power. Sasha Torres examines the complex relations between the television industry and the civil rights movement as a knot of overlapping interests. She argues that television coverage of the civil rights movement during 1955-1965 encouraged viewers to identify with black protestors and against white police, including such infamous villains as Birmingham's Bull Connor and Selma's Jim Clark. Torres then argues that television of the 1990s encouraged viewers to identify with police against putatively criminal blacks, even in its dramatizations of police brutality. Torres's pioneering analysis makes distinctive contributions to its fields. It challenges television scholars to consider the historical centrality of race to the constitution of the medium's genres, visual conventions, and industrial structures. And it displaces the analytical focus on stereotypes that has hamstrung assessments of television's depiction of African Americans, concentrating instead on the ways in which African Americans and their political collectives have actively shaped that depiction to advance civil rights causes. This book also challenges African American studies to pay closer and better attention to television's ongoing role in the organization and disorganization of U.S. racial politics.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Dramatized Societies: Quality Television in Spain and Mexico - Smith, Paul Julian (Liverpool University Press, 2016)
Over the last decade Spain and Mexico have both produced an extraordinary wealth of television drama. Drawing on both national practices of production and reception and international theories of textual analysis this book offers the first study of contemporary quality TV drama in two countries where television has displaced cinema as the creative medium that shapes the national narrative. As dramatized societies, Spain and Mexico are thus at once reflected and refracted by the new series on the small screen.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Espagne (corpus analysé); Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Muy buenas noches: Mexico, Television, and the Cold War - Gonzalez de Bustamante, Celeste (Nebraska Paperback, 2013)
By the end of the twentieth century, Mexican multimedia conglomerate Televisa stood as one of the most powerful media companies in the world. Most scholars have concluded that the company’s success was owed in large part to its executives who walked in lockstep with the government and the Partido Revolucionario Institucional (PRI), which ruled for seventy-one years. At the same time, government decisions regulating communications infrastructure aided the development of the television industry. In one of the first books to be published in English on Mexican television, Celeste González de Bustamante argues that despite the cozy relationship between media moguls and the PRI, these connections should not be viewed as static and without friction. Through an examination of early television news programs, this book reveals the tensions that existed between what the PRI and government officials wanted to be reported and what was actually reported and how. Further, despite the increasing influence of television on society, viewers did not always accept or agree with what they saw on the air. Television news programming played an integral role in creating a sense of lo mexicano (that which is Mexican) at a time of tremendous political, social, and cultural change. At its core the book grapples with questions about the limits of cultural hegemony at the height of the PRI and the cold war.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Nigger, Coon, Boy, Punk, Homo, Faggot, Black Man: Reconsidering Established Interpretations of Masculinity, Race, ans Sexuality Through Noah’s Arc - Cunningham, Mark D. (Watching While Black, 2012)
At best, our knowledge about the lives and experiences of Black gay men is limited to a series of stereotypes, snap judgments, and ridicule. In terms of television media product, this aforementioned knowledge has been packaged mostly within the framework of comedy: a red-leather-clad Eddie Murphy talking about the most effective ways to shield his ass from the gay male gaze in the 1983 HBO stand-up performance Delirious ; Damon Wayans and David Alan Grier’s effeminate film critics Blaine Edwards and Antoine Merriweather on the 1990s television variety show In Living Color ; fashionista panel members Miss J and Andre Leon Talley
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Blacks in the Future: Braving the Frontier of the Web Series - Acham, Christine (Watching While Black, 2012)
Television’s synergy with the Web initially seemed inconceivable to network executives. With the rise of Internet use, newspaper and magazine articles announced the impending death of television. While that was clearly hyperbole, network executives, though often anonymously, expressed their fears that Web content would siphon off viewership and thus advertising dollars generated by television programming. Fears may have been quelled with the evidence of the success of television shows first made available streaming on network websites and then for paid download through digital servers such as iTunes.
Keywords: 1-TV; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

A Black Cast Doesn’t Make a Black Show: City of Angels and the Plausible Deniability of Color-Blindness - Warner, Kristen J. (Watching While Black, 2012)
In a recent debate over the problematic characterization of Bonnie Bennett, the only Black female recurring character on the CW network series The Vampire Diaries (CW 2009), my challenger insisted that with all of the qualifiers I insisted she have, “maybe this is another hidden reason there are no minorities on television: everything becomes an issue and you just can’t win.” Indeed, the main qualifier I suggested that the series allow the character to possess—an innate sense of cultural difference—is difficult to grasp and maintain. However, I do not accept that just because race is difficult, it is
Keywords: 1-TV; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Two Different Worlds: Television as a Producer’s Medium - Coleman, Robin R. Means; Cavalcante, Andre M. (Watching While Black, 2012)
Although discourses regarding 1980s representations of Blackness on television heavily focus on The Cosby Show, its NBC spin-off series, A Different World, depicting student life at a historically Black college, was equally groundbreaking and deserving of critical attention. Looking to transfer the appeal and audience share of The Cosby Show to A Different World, the spin-off show’s first season centered on the life of The Cosby Show’s star Denise Huxtable (Lisa Bonet) at Hillman College. A Different World’s story provides an illuminating case study of the role and power of television producers, highlighting their influence over a show’s narrative and
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé)

The Importance of Roots - Pierson, Eric (Watching While Black, 2012)
In January 1977, I, along with over ninety million other Americans, watched at least one episode of the television miniseries Roots: The Saga of an American Family. Over the eight days of the broadcast, the audience grew, and debates regarding its impact filled media outlets. In the weeks and months after the show aired, the impact was measurable as many families sought out genealogists to research family histories and college campuses saw increased interest in African American Studies. Vernon Jordan, executive director of the National Urban League, commented, “ Roots was the single most spectacular educational experience in race relations in
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Introduction: I See Black People - Smith-Shomade, Beretta E. (Watching While Black, 2012)
This project has been engaging my thoughts for nearly a decade. I was forced to actually address it while sitting in our temporary home in Ile-Ife, Nigeria, watching world satellite TV with virtually no Blacks on it. In Nigeria, I became acquainted with Paris-based Fashion TV, U.S.-based Style Network, and the Australian production McLeod’s Daughters. Outside of M-Net’s Africa Magic, a network dedicated to showing Nollywood productions primarily, television was anything but Black. This whitening of the televisual frame, even in Black Africa, made me begin to consider the dearth of knowledge circulating about Black television programming, even when abundance
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Mexico: The Melodrama on Netflix: Transformation or Evolution? - Orozco, Guillermo; Gómez, Gabriela; Franco, Darwin (Obitel 2020: Melodrama in Times of Streaming, 2020)
The high expectations of change caused by the victory of An- drés Manuel López Obrador for the presidency of Mexico have not been translated into any substantive modification in the Mexican media ecosystem or in the communication policies that have led the media-state relations in the country. However, what has been modi- fied/conditioned is the setting of the daily news agenda, since the new president has imposed a political-governmental communica- tion framework by holding morning press conferences, in which, with little opposition from the media, he sets the topics to be dis- cussed on a daily basis. It has created various problems with those media and/or journalists that have questioned the stances he has adopted, his plans and projects. The conflict escalated to such an extent that López Obrador has called his opponents “prensa fifí” (“snob press”), pointing out in a very clear way that these are ac- tors who only seek to defend the privileges lost during his govern- ment by conservative media, or, as he has called them: “la mafia del poder” (“the power mafia”).
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Mexique (corpus analysé); Mexique (lieu de production du savoir); _Nettoyé

Interpreting Cubanness, Americanness, and the Sitcom: WPBT-PBS’s ¿Qué pasa U.S.A.? (1975–1980) - Rivero, Yeidy M. (Global Television Formats: Understanding Television Across Borders, 2012)
I was about 10 or 11 years old when I, together with my parents, religiously tuned in weekly to the situation comedy ¿Qué pasa U.S.A.? While I do not recall the speciﬁc year the show aired in Puerto Rico, I do remember that it was broadcast on WIPR-Channel 6, the island’s public television station. Watching one of my favorite sitcoms on what I then considered the boring channel was rather odd. However, I never thought it strange that the Peñas, ¿Qué pasa U.S.A.? ’s working-class three-generation Cuban/Cuban-American family, resided in Miami or that some of the characters communicated bilingually in English and Spanish. For me, ¿Qué pasa U.S.A.? was a show that resembled other locally produced situation comedies broadcast on commercial television, with the difference that the Peña family were Cuban immigrants who, instead of residing in Puerto Rico (like some of my childhood friends), lived in Miami (like many of my friends’ relatives). Probably as a result of the principal characters’ cultural references and their accents in Spanish, I decoded ¿Qué pasa U.S.A.? as a Cuban sitcom. Fast-forward to 2004. I was invited to write a 500-word encyclopedia entry on ¿Qué pasa U.S.A.? Without having any information on the show at hand, I immediately accepted. This was an opportunity to revisit a program I loved. After conducting the research I realized the uniqueness of ¿Qué pasa U.S.A.? Sponsored by the U.S. Ofﬁce of Education Emergency School Assistance Act– Television Program (ESAA-TV), ¿Qué pasa U.S.A.? —considered the ﬁrst bilingual situation comedy broadcast on U.S. television— addressed the culturalgenerational misunderstandings and the socio-cultural adjustments endured by the Peñas, a 1960 Cuban exile family.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Cuba (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Du « dix-neuf » au « nineteen ». Une étude comparative des versions québécoise francophone et canadienne anglophone de la série télévisée 19-2 - Boisvert, Stéfany (Canadian Journal of Film Studies/Revue Canadienne d'études cinématographiques, 2016)
Cet article propose une étude comparative de la première saison de la série policière québécoise primée 19-2 (Ici Radio-Canada Télé, 2011-2015) et de son adaptation canadienne anglophone (Bravo, 2014-). L’étude des deux séries 19-2 permet d’investiguer, à travers un exemple récent, le processus d’adaptation télévisuelle au Canada. Les similitudes narratives et esthétiques entre les deux séries sont tout d’abord brièvement présentées: l’histoire et les arcs narratifs sont quasi identiques, la plupart des personnages conservent les mêmes noms, sans compter que les stratégies narratives marquantes de cette œuvres ont été pour la plupart reproduites dans la nouvelle version. Ces deux œuvres, appréhendées en tant que « performances » distinctes, sont ensuite analysées à travers le prisme du genre. L’analyse de quelques scènes clés et arcs narratifs permettra de démontrer que ces deux productions sont très différentes en ce qui concerne leur construction narrative de masculinités télévisées – particulièrement leur négociation différentielle de conceptions hégémoniques des identités – et leur représentation des rapports hommes-femmes.
Keywords: 1-TV; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Canada (corpus analysé); Canada (lieu de production du savoir); _Nettoyé

New Flows in Global TV - Moran, Albert (Intellect Books, 2009)
New Flows in Global TV provides a pioneering investigation into television distribution worldwide and the global trade in television program formats. Topics include explorations of how shows like Who Wants to Be a Millionaire? and Big Brother are reformatted for audiences in diverse markets such as Argentina, South Africa, the Middle East, and China; the international circulation of Dallas in the 1980s; and Australian and United Kingdom programming exports in the last decade. Moran argues that distribution is the crucial link in a chain that dictates the consumption and purchase of television content. Consequently, New Flows in Global TV will be a key text for scholars of global media, providing comprehensive insight into the cultural, social and economic exchanges underlying media programming.
Keywords: 1-TV; 2-Étude des industries culturelles; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Understanding the Global TV Format - Moran, Albert; Malbon, Justin (Intellect Books, 2006)
This volume presents a series of papers concerned with the interrelations between the postmodern and the present state of art and design education. Spanning a range of thematic concerns, the book reflects upon existing practice and articulates revolutionary prospects potentially viable through a shift in educative thinking.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

McTV: Understanding the Global Popularity of Television Formats - Waisbord, Silvio (Television & New Media, 2004)
Globalization has intensified interconnectivity among television industries worldwide. Interconnectivity happens through structural and institutional linkages among television systems and industries worldwide, resulting in an increasingly integrated global business governed by similar practices and goals. The dynamics are reflected in the popularity of television formats. On the surface, global dissemination of formats may suggest not only the global integration of the economy of the industry but also the standardization of content. A dozen media companies are able to do business worldwide by selling the same idea, and audiences seem to be watching national variations of the same show. At a deeper level, however, formats attest to the fact that television still remains tied to local and national cultures. Bringing up examples of Latin American cases, this article argues that television is simultaneously global and national, shaped by the globalization of media economics and the pull of local and national cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; Argentine (corpus analysé); Brésil (corpus analysé); Mexique (corpus analysé); Royaume-Uni (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)